The Impact of Motivation and Work Discipline on Employee Performance at the Financial Services Authority Office - Adinda Dwi Astuti; Cecep Haryoto (MES Management Journal, 2025)
This study aims to examine the effect of work motivation and work discipline on employee performance at the Financial Services Authority Office. Using a quantitative associative approach, data were collected from 60 employees through questionnaires and analyzed using multiple linear regression with SPSS. The results show that work motivation has a positive and significant effect on employee performance (t = 9.704, p < 0.05), and work discipline also has a positive and significant effect (t = 6.745, p < 0.05). Furthermore, the F-test results (F = 95.376, p < 0.05) indicate that motivation and work discipline simultaneously have a significant effect on employee performance. These findings suggest that improving motivation and strengthening work discipline are essential to enhancing employee performance at the Financial Services Authority Office.